'Communities are attempting to tackle the crisis': a scoping review on community plans to prevent and reduce opioid-related harms. Issue 9 (12th September 2019) - Leece, Pamela; Khorasheh, Triti; Paul, Nimitha; Keller-Olaman, Sue; Massarella, Susan; Caldwell, Jayne; Parkinson, Michael; Strike, Carol; Taha, Sheena; Penney, Greg; Henderson, Rita; Manson, Heather
Abstract : Objectives: We sought to understand the implementation of multifaceted community plans to address opioid-related harms. Design: Our scoping review examined the extent of the literature on community plans to prevent and reduce opioid-related harms, characterise the key components, and identify gaps. Data sources: We searched MEDLINE, Embase, PsycINFO, CINHAL, SocINDEX and Academic Search Primer, and three search engines for English language peer-reviewed and grey literature from the past 10 years. Eligibility criteria: Eligible records addressed opioid-related harms or overdose, used two or more intervention approaches (eg, prevention, treatment, harm reduction, enforcement and justice), involved two or more partners and occurred in an Organisation for Economic Co-operation and Development country. Data extraction and synthesis: Qualitative thematic and quantitative analysis was conducted on the charted data. Stakeholders were engaged through fourteen interviews, three focus groups and one workshop. Results: We identified 108 records that described 100 community plans in Canada and the USA; four had been evaluated. Most plans were provincially or state funded, led by public health and involved an average of seven partners. Commonly, plans used individual training to implement interventions. Actions focused on treatment and harm reduction, largely to increase access to addiction services and naloxone. Among specific groups, people in conflict with the law were addressed most frequently. Community plans typically engaged the public through in-person forums. Stakeholders identified three key implications to our findings: addressing equity and stigma-related barriers towards people with lived experience of substance use; improving data collection to facilitate evaluation; and enhancing community partnerships by involving people with lived experience of substance use. Conclusion: Current understanding of the implementation and context of community opioid-related plans demonstrates a need for evaluation to advance the evidence base. Partnership with people who have lived experience of substance use is underdeveloped and may strengthen responsive public health decision making.